MiRNA-200c mediates mono-butyl phthalate-disrupted steroidogenesis by targeting vimentin in Leydig tumor cells and murine adrenocortical tumor cells. (22nd January 2016) - Lu, Hongchao; Zhang, Chang; Hu, Yanhui; Qin, Heng; Gu, Aihua; Li, Yuan; Zhang, Lulu; Li, Zhong; Wang, Yubang
Highlights: Low dose of MBP increased steroidogenesis by facilitating cholesterol transfer process. Low dose of MBP decreased miRNA-200c expression in MLTC-1 and Y1 cells. Low dose of MBP disrupted steroidogenesis through upregulated vimentin by miRNA-200c. Abstract: The reproductive toxicity of plasticizer di- n -butyl phthalate (DBP) and its active metabolite monobutyl phthalate (MBP) has been demonstrated in rodents. The objective of this study was to explore roles of vimentin and miRNA-200c in steroidogenesis interfered by MBP. Mouse Leydig tumor cells (MLTC-1) and murine adrenocortical tumor cells (Y1) were employed and exposed to various levels of MBP (10 −7, 10 −6, 10 −5 and 10 −4 M). Steroid hormone production was increased significantly when MLTC-1 and Y1 cells were exposed to MBP at 10 −7 M. Additionally, vimentin and steroidogenic acute regulatory protein (StAR) expressions were upregulated at the same dose. It was found that MBP increased the steroidogenesis by facilitating the cholesterol transfer process by vimentin. In contrast, miRNA-200c expression was depressed at doses of MBP (10 −7 M) in both cells. Moreover, vimentin expression and progesterone production were increased in both MLTC-1 and Y1 cells after miRNA-200c expression was artificially inhibited. These results strongly suggested that MBP raised steroid hormone synthesis via upregulated vimentin by miRNA-200c.